Combined use of elemental profiles and stable isotope ratios for the botanical and commercial discrimination of gum Arabic. (August 2020) - Perini, M.; Bertoldi, D.; Nardin, T.; Pianezze, S.; Ferrari, G.; Larcher, R.
Abstract: Gum arabic (GA) is a natural, edible gum with particular characteristics resulting from its complex mixture of polysaccharides and glycoproteins. GA is used extensively in several fields and global demand is steadily increasing; for this reason, the determination of GA origin is fundamental to counteract commercial frauds and ensure food safety. The purpose of the study was to investigate whether elemental and isotopic profiles could discriminate, first, between GA produced from plants belonging to the same genus ( Acacia ) but to 2 different species ( A. senegal, SN; A. seyal, SY), and, second, considering only GA of the same botanical origin (SN), between gums produced from different geographic areas (Kordofan region in Sudan vs other Sub-Saharan areas) and commercially resulting in products with different characteristics. The Principal Component Analysis (PCA), combining elemental and stable isotope profiles, could clearly separate the 45 gum samples in 2 clusters corresponding to the botanical species of origin. Results were screened using a partial least squares regression (PLS-R) model developed following the leave-one-out cross-validation approach and including a validation subset of 8 samples. All the calibration and validation samples showed a 100% correct classification, both for SN and SY. Furthermore, the PCA, using only the C, N, Cs, Mg and Na content, could adequately discriminate the SN samples according to their geographic origin, distinguishing the Kordofan samples, traditionally renowned as top-quality products, from the generic gum samples produced in other Sub-Saharan areas. Graphical abstract: Image 1 Highlights: Elemental and isotopic analysis of gum arabic for botanical discrimination. The PLS-R model achieved 100% correct classification for gum samples. C, N, Cs, Mg and Na content allowed the discrimination of Kordofan gum.